Augustus and the creation of the Roman Empire : A brief history with documents - Mellor, Ronald (Boston Bedford/St. Martin's, 2006)
Offering multiple viewpoints of the rise, achievements, and legacy of Caesar Augustus and his empire, Augustus and the Creation of the Roman Empire encourages the examination of such subjects as the military in war and peacetime, the social and cultural context of political change, the reform of administration, and the personality of the emperor himself.
Includes bibliography and index
Keywords: Tham khảo